2023
DOI: 10.3390/plants12071474
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of the Rose SWEET Gene Family and Their Different Expression Profiles in Cold Response between Two Rose Species

Abstract: Sugars Will Eventually be Exported Transporter (SWEET) gene family plays indispensable roles in plant physiological activities, development processes, and responses to biotic and abiotic stresses, but no information is known for roses. In this study, a total of 25 RcSWEET genes were identified in Rosa chinensis ‘Old Blush’ by genome-wide analysis and clustered into four subgroups based on their phylogenetic relationships. The genomic features, including gene structures, conserved motifs, and gene duplication a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Liu et al analyzed 204 HhMYB family members in Hibiscus hamabo using RNA-seq and a qRT-PCR, and found that HhMYB was involved in plant responses to salt and drought stress to varying degrees [13]. Song et al identified and analyzed 25 SWEET genes in Rosa chinensis 'Old Blush', and through a transcriptome analysis, SWEET2a and SWEET10c were found to be candidate genes involved in the rose's ability to tolerate cold conditions [14].…”
Section: Gene Family Identificationmentioning
confidence: 99%
“…Liu et al analyzed 204 HhMYB family members in Hibiscus hamabo using RNA-seq and a qRT-PCR, and found that HhMYB was involved in plant responses to salt and drought stress to varying degrees [13]. Song et al identified and analyzed 25 SWEET genes in Rosa chinensis 'Old Blush', and through a transcriptome analysis, SWEET2a and SWEET10c were found to be candidate genes involved in the rose's ability to tolerate cold conditions [14].…”
Section: Gene Family Identificationmentioning
confidence: 99%
“…There are numerous members of the SWEET gene family in higher plants, and studies on the SWEET gene family have been reported: There are 17, 21, 24, 29, 34, 27, 17, 27, 16, 22, 20, 19, 23, 25, and 25 SWEETs identified in Arabidopsis thaliana [10], rice [16], maize [17], tomato [18], Brassica rapa [19], garlic [20], grapes [21], apples [22], litchi [23], watermelon [24], longan [25], jujube [7], Bletilla striata [26], Dendrobium officinale [27], and rose [28], respectively. The members of the SWEET gene family have the specificity of space-time and tissue expression, and there are obvious differences in the types of transported sugar [29].…”
Section: Introductionmentioning
confidence: 99%
“…The SWEETs gene family was initially identified in Arabidopsis thaliana [3]. To date, with a large number of plant genomes sequenced, the systematic genome-wide identification of SWEET genes has been reported in many crops, vegetables, fruits, and flowers, such as Oryza sativa [7], Zea mays [8], Glycine max [9], Brassica oleracea [10], Solanum lycopersicum [11], Solanum tuberosum [12], Cucumis sativus [13], Musa acuminate [14], Malus domestica [15], Litchi chinensis [16], Vitis vinifera [17], Rosa chinensis [18], Dendrobium chrysotoxum [19], Hemerocallis fulva [20], and Petunia axillaris [21]. Previous studies have shown that SWEET genes are involved in multiple physiological processes related to phloem loading [22][23][24][25], nectar secretion [6], pollen/flower development [26][27][28], seed/fruit development [29][30][31][32][33][34], senescence [35][36][37], modulating gibberellins response [38,39], and abiotic stress response [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%